Measures of Designing an English Language Course for Teachers of Madrassas (Religious Schools) - Farooqi, Muhammad Ali; Dr Muhammad Azeem (MEI, 2023)
English being an international language is really a good source of communication and instruction. The new dimensions of communication, teaching and learning with ever-changing demands of the masses have made English a need of the day. The students of all departments must be proficient in English language to achieve the desired goals. The present research highlights the importance of English language for the teacher of Madrassas (religious schools in Islam). The researchers have examined various Madrassas and found the teachers of these Madrassas are not well- acquainted with the language of the world. So they are not able to convey their thoughts at international level. The researchers evaluated the syllabus of these Madrassas and finally discovered that the present syllabus was missing an adequate course of English language. This research article has especially been written as a guideline for designing an English language course for the teachers of Madrassas on experimental basis. The research ends with a proposed English language course on English for specific purpose (ESP) basis to enhance the expertise of the teachers of Madrassas in English.